Glioblastoma-derived exosomes promote lipid accumulation and induce ferroptosis in dendritic cells via the NRF2/GPX4 pathway - Yang, Jian; Zhang, Mingqi; Zhang, Xuying; Zhou, Yue; Ma, Tingting; Liang, Jia; Zhang, Jinyi (Frontiers in Immunology, 2024)
Glioblastoma-derived exosomes (GDEs), containing nucleic acids, proteins, fatty acids and other substances, perform multiple important functions in glioblastoma microenvironment. Tumor-derived exosomes serve as carriers of fatty acids and induce a shift in metabolism towards oxidative phosphorylation, thus driving immune dysfunction of dendritic cells (DCs). Lipid peroxidation is an important characteristic of ferroptosis. Nevertheless, it remains unclear whether GDEs can induce lipid accumulation and lipid oxidation to trigger ferroptosis in DCs. In our study, we investigate the impact of GDEs on lipid accumulation and oxidation in DCs by inhibiting GDEs secretion through knocking down the expression of Rab27a using a rat orthotopic glioblastoma model. The results show that inhibiting the secretion of GDEs can reduce lipid accumulation in infiltrating DCs in the brain and decrease mature dendritic cells (mDCs) lipid peroxidation levels, thereby suppressing glioblastoma growth. Mechanistically, we employed in vitro treatments of bone marrow-derived dendritic cells (BMDCs) with GDEs. The results indicate that GDEs decrease the viability of mDCs compared to immature dendritic cells (imDCs) and trigger ferroptosis in mDCs via the NRF2/GPX4 pathway. Overall, these findings provide new insights into the development of immune-suppressive glioblastoma microenvironment through the interaction of GDEs with DCs.